F/A - 18 E/F Super Hornet - Mckinney, Donna ([S.l.] : TORQUE, 2024)
The Super Hornet is a speedy fighter jet. It flies at supersonic speeds! In this hi-lo text, readers will learn what this high-powered military aircraft can do. Vibrant, high-quality images bring this aircraft to life for readers to experience for themselves. Special features highlight the aircraft's weapons, technology, and size. A two-page ending spread explores the capabilities and equipment of this superfast jet!
112864